DIFFERENTIATION OF RESPONSIBILITY AS AN EXPRESSION OF THE PRINCIPLE OF JUSTICE - Yu. Bokovnya, Alexandra; R. Sundurov, Fedor (Gênero & Direito, 2019)
The proposed article studies the differentiation of criminal responsibility from the standpoint of implementing the principle of justice. The authors point out, along with positive decisions of the legislator, to the imperfection of the regulation in the Criminal Code of the Russian Federation of differentiation of criminal responsibility from the standpoint of the principle of justice.